PENGARUH GROWTH OPPORTUNITY, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR SEKTOR TEKSTIL DAN GARMEN DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Roy Ariando Saragih; Haryetti Haryetti; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to determine and analyze about the influence of growth opportunity, profitability,and capital structure to firm value with good corporate governance as moderating variable at manufacture industry sector textile and garment 2012-2016 period. This study uses secondary data in Annual Report from 2012-2016 obtained from the website of Indonesian Stock Exchange or www.idx.co.id. The population in this study amounted to 19 textile and garment companies listed on the Indonesian Stock Exchange with sampling techniques using purposive sampling obtained by 15 companies Hypothesis testing in this study using multiple linear regression and moderating regression (MRA) with t-test and coefficient determination test processed using SPSS 20. The results of this study indicate that (1) Growth Opportunity does not affect to the firm value with siginicant value 0,258 > 0,05 (2) Profitability has an affect to the firm value with siginicant value 0,026 < 0,05 (3) Capital Structure does not affect to the firm value with siginicant value 0,093 > 0,05(4) Good Corporate Governance has an affect to the firm value with siginicant value 0,009 < 0,05(5) Good Corporate Governance does not moderate the relationship of growth opportunity to firm value with siginicant value 0,265 > 0,05 (6) Good Corporate Governance does not moderate the relationship of profitability to firm value with siginicant value 0,296 > 0,05 (7) Good Corporate Governance moderate the relationship of capital structure to firm value with siginicant value 0,05 < 0,05.Keywords : Growth Opportunity, Profitability, Capital Structure, Good Corporate Governance, Firm Value